LAYANAN INFORMASI OLEH GURU PEMBIMBING TENTANG PENGENDALIAN STRES DALAM BELAJAR DI SMPN 2 PONTIANAK - Simare Mare, Gresmid; Astuti, Indri; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This study aims to obtain an objective picture of Information Services by Supervising Teachers About Controlling Stress in Learning in Class VIII SMPN 2 Pontianak . The general problem in this study is "What is Information Services by Supervising Teachers for Stress Control in Learning in Class VIII SMPN 2 Pontianak 2016/2017 Academic Year. The method used is descriptive method with a quantitative approach. The sample in this study were 34 students. Data collection techniques in this study are direct communication techniques and indirect communication techniques. Data collection tools in this study were questionnaires, and interviews. The results of the data analysis showed that the information service carried out by the tutor to control stress on students of SMPN 02 Pontianak reached an actual score of 1058 from an ideal maximum score of 1394, meaning that it reached 75.89% in the Good category. Obstacles faced in the implementation of information services by the mentor teacher to control stress in learning is the time limitation of the mentor teacher in developing material to control stress in learning, caused by the tutor teacher does not get hours of class entry, lack of cooperation with teachers in the field of study, books the library is very limited.            Keywords: Information Services, Controlling Stress